Unlocking Work Autonomy: A Hybrid Approach for Sustainable Job Satisfaction in the Post-Covid Era - Purba, Sylvia Diana; Nilawati, Levi; Nugroho, Yohanes Arianto Budi; Budianto, Erin; Geat, Johan Lim Kii (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2024)
This research aims to design a hybrid work model with a task-characteristic autonomy job design. Remote work or Work from Anywhere (WFA) is widely used, as the Covid-19 pandemic accelerated this method. For some people, the WFA method is enjoyable because it can provide freedom to organize work methods, allowing for high work autonomy. However, some people also feel that working remotely creates a feeling of isolation and boredom and reduces job satisfaction. The hybrid method will increase work autonomy, work-life balance, and job satisfaction. This research is aimed at employees in Jakarta and surrounding areas who can work hybrid. The research population is difficult to calculate, so the sampling method is purposive, and the sampling technique is convenience method. Hypothesis testing was done using Structural Equation Modeling (SEM). The research results prove that applying the hybrid method can significantly increase job satisfaction by fully mediating the task characteristic autonomy and the work-life balance variables. Therefore, applying the Hybrid method is an option because, in the next decade, the world of work will increasingly be dominated by Gen Y and Gen Z.